Effect of Dexmedetomidine Alone for Intravenous Patient-Controlled Analgesia After Gynecological Laparoscopic Surgery: A Consort-Prospective, Randomized, Controlled Trial. Issue 19 (May 2016) - Wang, Xiuqin; Liu, Wenjuan; Xu, Zan; Wang, Fumei; Zhang, Chuanfeng; Wang, Baosheng; Wang, Kaiguo; Yu, Jingui
Abstract : Abstract: Gynecological laparoscopic surgery is minimally invasive compared with open surgical approaches, but postoperative pain is generally undermanaged. Pain management strategies related to the procedure-specific efficacy are needed. Many studies have shown that dexmedetomidine (DEX) has opioid-sparing properties. It is not clear whether DEX used alone for intravenous patient-controlled analgesia (PCA) could reduce postoperative pain after an invasive procedure. We hypothesized that DEX alone would reduce postoperative pain in women patients undergoing an elective gynecological laparoscopic procedure. This CONSORT-prospective randomized controlled clinical study aimed to investigate the effects of DEX alone for intravenous PCA after gynecological laparoscopic operation. Forty women patients scheduled for elective gynecological laparoscopy were enrolled into the study at Shandong Cancer Hospital and Institute and randomly allocated into two groups (n = 20 each). In the DEX group (group D), the intravenous PCA protocol was DEX 0.25 μg/kg/h diluted to 100 mL in 0.9% saline. In the fentanyl group (group F), the PCA protocol was fentanyl 20 μg/kg diluted to 100 mL in 0.9% saline. The primary outcome was the mean pain score on a visual analogue scale (VAS) at 6 hours after the operation. The secondary outcomes included the Ramsay sedation score, the incidence of postoperative nausea and vomiting (PONV), satisfaction with pain control, and time to recovery of gastrointestinal function. There were no significant differences in the patients' characteristics and intraoperative measurements ( P  > 0.05). No patients received rescue analgesic. The mean VAS scores at 6 hours post-operatively were not significantly different between the groups ( P  > 0.05). The incidence of PONV was less in group D than in group F ( P  < 0.05). The Ramsay sedation scores were not significantly between the groups ( P  > 0.05). Satisfaction with pain control was higher and time to recovery of gastrointestinal function was lower in group D ( P  < 0.05). DEX alone is effective for intravenous patient-controlled analgesia after gynecological laparoscopic surgery without a change in sedation and with fewer side effects, and this effect was associated with better satisfaction with postoperative pain control and earlier recovery of gastrointestinal function.